From reading to writing: Evaluating the Writer's Craft as a means of assessing school student writing - Pauline Sangster, Graeme Trousdale & Charles Anderson (Journal of Writing Research, 2012)
This article reports on part of a study investigating a new writing assessment, the Writer's Craft, which requires students to read a stimulus passage and then write a continuation adopting the style of the original. The article provides a detailed analysis of stimulus passages employed within this assessment scheme and students' written continuations of these passages. The findings reveal that this is a considerably more challenging assessment writing task than has previously been recognised; and that questions arise concerning the nature of the stimulus passages and the extent to which the assessment criteria captured what the students had achieved in their writing. The implications of these findings are discussed and recommendations are made.